Contribution of dermal ethanol absorption during laboratory-controlled high-frequency use of alcohol-based hand rubs followed by glove use - Paul T. J. Scheepers; Kirsten Lassing; Martien H. F. Graumans; Sander H. P. Driessen; Antzelina Gkintsev; Ioanna Konstantinou; Valérie Leermakers; Hilde Onstek; Maxime Sülter; Lotte van den Oord; Chariya van Dolder; Hendrik Jan Jansen; et al. (Archives of Toxicology, 2026)
The safety of using ethanol-based products for hygienic hand disinfection in healthcare workers is controlled by restricting air levels. This raises the question of whether these workers are sufficiently protected against potential dermal absorption. The study aim was to determine the contribution of the dermal route to the total uptake of ethanol. A laboratory-controlled study of 25 sequential alcohol-based-hand-rubs (ABHRs) with subsequent intermediate glove use was conducted in seven healthcare workers. Two exposure conditions were compared: hands and forearms placed inside a laboratory fume hood preventing inhalation (skin-only condition) and the same procedure but outside the fume hood to allow inhalation (native condition). The hand hygiene product contained 84% ethanol and 1% ethanol-d6 added to verify exogenous origin. Inhalation exposure was measured by personal air sampling. Blood was collected at baseline, during exposure and a post-exposure wash-out period and analysed for ethanol and ethanol-d6 by HS-GC-MS. The contribution of dermal uptake was assessed by comparing the area-under-curve (AUC) of blood ethanol concentrations in the skin-only condition with that in the native condition within each study participant. Inhalation exposure in the breathing zone was (mean ± sd): 5.3 ± 3.6 mg/m 3 in the skin-only condition and 120 ± 7 mg/m 3 in the native condition. The corresponding AUCs for blood ethanol concentrations were 1400 ± 1100 and 3300 ± 2300 (mg/L)*min ( p = 0.014), respectively, indicating a contribution from dermal absorption of 43 ± 28% ( N = 7). For ethanol-d6 these values were 17 ± 4 and 48 ± 17 (mg/L)*min ( p = 0.064), respectively, with a contribution of dermal uptake of 40 ± 16% ( N = 3). In conclusion, high-frequency ABHRs lead to significant dermal absorption of ethanol.

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Extremophiles in a changing world - D. A. Cowan; S. V. Albers; G. Antranikian; H. Atomi; B. Averhoff; M. Basen; A. J. M. Driessen; M. Jebbar; Z. Kelman; M. Kerou; J. Littlechild; V. Müller; et al. (Extremophiles, 2024)
Extremophiles and their products have been a major focus of research interest for over 40 years. Through this period, studies of these organisms have contributed hugely to many aspects of the fundamental and applied sciences, and to wider and more philosophical issues such as the origins of life and astrobiology. Our understanding of the cellular adaptations to extreme conditions (such as acid, temperature, pressure and more), of the mechanisms underpinning the stability of macromolecules, and of the subtleties, complexities and limits of fundamental biochemical processes has been informed by research on extremophiles. Extremophiles have also contributed numerous products and processes to the many fields of biotechnology, from diagnostics to bioremediation. Yet, after 40 years of dedicated research, there remains much to be discovered in this field. Fortunately, extremophiles remain an active and vibrant area of research. In the third decade of the twenty-first century, with decreasing global resources and a steadily increasing human population, the world’s attention has turned with increasing urgency to issues of sustainability. These global concerns were encapsulated and formalized by the United Nations with the adoption of the 2030 Agenda for Sustainable Development and the presentation of the seventeen Sustainable Development Goals (SDGs) in 2015. In the run-up to 2030, we consider the contributions that extremophiles have made, and will in the future make, to the SDGs.

Conceptualising boundary work activities to enhance credible, salient and legitimate knowledge in sustainability transdisciplinary research projects - Lisa M. Andrews; Stefania Munaretto; Heleen L.P. Mees; Peter P.J. Driessen (Environmental Science & Policy, 2024)

Unraveling the multiplicity of geranylgeranyl reductases in Archaea: potential roles in saturation of terpenoids - Alka Rao; Arnold J. M. Driessen (Extremophiles, 2024)
The enzymology of the key steps in the archaeal phospholipid biosynthetic pathway has been elucidated in recent years. In contrast, the complete biosynthetic pathways for proposed membrane regulators consisting of polyterpenes, such as carotenoids, respiratory quinones, and polyprenols remain unknown. Notably, the multiplicity of geranylgeranyl reductases (GGRs) in archaeal genomes has been correlated with the saturation of polyterpenes. Although GGRs, which are responsible for saturation of the isoprene chains of phospholipids, have been identified and studied in detail, there is little information regarding the structure and function of the paralogs. Here, we discuss the diversity of archaeal membrane-associated polyterpenes which is correlated with the genomic loci, structural and sequence-based analyses of GGR paralogs.

Predictive modeling toward refinement of behavior-based pain assessment in horses - Pedro Henrique Esteves Trindade; Paula Barreto da Rocha; Bernd Driessen; Sue M. McDonnell; Klaus Hopster; Laura Zarucco; Miguel Gozalo-Marcilla; Charlotte Hopster-Iversen; Thamiris Kristine Gonzaga da Rocha; Marilda Onghero Taffarel; Bruna Bodini Alonso; Stijn Schauvliege; et al. (Applied Animal Behaviour Science, 2023)

Influences of adjacent suburbia, fire regimes and vegetation on the mammals of a peri-urban reserve - Jamie B. Kirkpatrick; Michael M. Driessen; Peter J. Jarman; Lauren Jakob (Urban Ecosystems, 2023)
Urban development is thought to negatively affect most native mammals. Here we assess whether adjacent suburbia, fire regime and vegetation influence the activity of mammal species in a reserve in Hobart, Tasmania, Australia. We used multiple regression to analyse the relationship between distance from houses, fire history, vegetation structure and floristics, and mammal activity, derived from camera visits and signs. Animal diggings and visits by long-nosed potoroos, southern brown bandicoots and cats were greater close to houses, while visits by red-necked wallabies, rufous-bellied pademelons, brushtail possums and short-beaked echidnas were not. The structure of the vegetation, particularly related to shelter, was important in many models. Many models also included floristic ordination axes that reflected drainage, fire regime and distance from high-density housing. Positive relationships between the introduced predatory cat and some of its potential native prey animals may reflect the influences of close proximity to suburbia, such as elevated domestic mesopredator populations, and elevated resource availability in domestic gardens. Our results suggest that urban areas can have a valuable role in nature conservation, despite, or because of, their effects on remnant native ecosystems.

The catalytic and structural basis of archaeal glycerophospholipid biosynthesis - Niels A. W. de Kok; Arnold J. M. Driessen (Extremophiles, 2022)
Archaeal glycerophospholipids are the main constituents of the cytoplasmic membrane in the archaeal domain of life and fundamentally differ in chemical composition compared to bacterial phospholipids. They consist of isoprenyl chains ether-bonded to glycerol-1-phosphate. In contrast, bacterial glycerophospholipids are composed of fatty acyl chains ester-bonded to glycerol-3-phosphate. This largely domain-distinguishing feature has been termed the “lipid-divide”. The chemical composition of archaeal membranes contributes to the ability of archaea to survive and thrive in extreme environments. However, ether-bonded glycerophospholipids are not only limited to extremophiles and found also in mesophilic archaea. Resolving the structural basis of glycerophospholipid biosynthesis is a key objective to provide insights in the early evolution of membrane formation and to deepen our understanding of the molecular basis of extremophilicity. Many of the glycerophospholipid enzymes are either integral membrane proteins or membrane-associated, and hence are intrinsically difficult to study structurally. However, in recent years, the crystal structures of several key enzymes have been solved, while unresolved enzymatic steps in the archaeal glycerophospholipid biosynthetic pathway have been clarified providing further insights in the lipid-divide and the evolution of early life.

Experimentally manipulated food availability affects offspring quality but not quantity in zebra finch meso-populations - Yoran H. Gerritsma; Merijn M. G. Driessen; Marianthi Tangili; Sietse F. de Boer; Simon Verhulst (Oecologia, 2022)
Food availability modulates survival, reproduction and thereby population size. In addition to direct effects, food availability has indirect effects through density of conspecifics and predators. We tested the prediction that food availability in isolation affects reproductive success by experimentally manipulating food availability continuously for 3 years in zebra finches ( Taeniopygia guttata ) housed in outdoor aviaries. To this end, we applied a technique that mimics natural variation in food availability: increasing the effort required per food reward without affecting diet. Lower food availability resulted in a slight delay of start of laying and fewer clutches per season, but did not affect clutch size or number of offspring reared per annum. However, increasing foraging costs substantially reduced offspring growth. Thus, food availability in isolation did not impact the quantity of offspring reared, at the expense of offspring quality. Growth declined strongly with brood size, and we interpret the lack of response with respect to offspring number as an adaptation to environments with low predictability, at the time of egg laying, of food availability during the period of peak food demand, typically weeks later. Manipulated natal brood size of the parents did not affect reproductive success. Individuals that were more successful reproducers were more likely to survive to the next breeding season, as frequently found in natural populations. We conclude that the causal mechanisms underlying associations between food availability and reproductive success in natural conditions may be more complex than usually assumed. Experiments in semi-natural meso-populations can contribute to further unravelling these mechanisms.

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

Appropriateness of empirical antibiotic therapy and added value of adjunctive gentamicin in patients with septic shock: a prospective cohort study in the ICU - Rob G. H. Driessen; Rald V. M. Groven; Johan van Koll; Guy J. Oudhuis; Dirk Posthouwer; Iwan C. C. van der Horst; Dennis C. J. J. Bergmans; Ronny M. Schnabel (Infectious Diseases, 2021)

Comment on: Gao B, Lu Q, Wan R, Wang Z, Yang Y, Chen Z, Wang Z. “Monthly versus quarterly fremanezumab for the prevention of migraine: a systemic review and meta-analysis from randomized controlled trials”. Naunyn Schmiedebergs Arch Pharmacol. 2021 Apr;394(4):819–828. Epublished November 2020 - Steve Barash; Verena Ramirez Campos; Xiaoping Ning; Maurice T. Driessen; Lynda J. Krasenbaum; Karen Carr; Joshua M. Cohen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Recently, Gao et al. published an article titled “Monthly versus quarterly fremanezumab for the prevention of migraine: a systemic review and meta-analysis from randomized controlled trials” which concluded that monthly administration of fremanezumab led to significant reduction in monthly migraine days (MMD) when compared to quarterly fremanezumab. We have noted a critical flaw in Gao et al. meta-analysis wherein the authors have mistakenly utilized standard error values in place of standard deviation values in performing their pooled analyses. This error directly impacts the study results and conclusions. In this brief communication, we present revised analysis using correct methods. Using the correct SD values, our pooled analysis showed no significant difference in mean change from baseline in MMD between the two fremanezumab dosing regimens ( P = 0.17). Furthermore, in the corrected subgroup analyses by type of migraine, there were no significant differences in mean change from baseline in MMD between monthly fremanezumab and quarterly fremanezumab (chronic migraine, P = 0.50; episodic migraine, P = 0.69). Overall, results from our corrected meta-analyses show that there is no significant difference in migraine prevention efficacy between monthly and quarterly fremanezumab dosing.

EXPRESSION OF CONCERN: InsectChange: a global database of temporal changes in insect and arachnid assemblages - Roel van Klink; Diana E. Bowler; Orr Comay; Michael M. Driessen; S. K. Morgan Ernest; Alessandro Gentile; Francis Gilbert; Konstantin B. Gongalsky; Jennifer Owen; Guy Pe'er; Israel Pe'er; Vincent H. Resh; et al. (Ecology, 2021)
Insects are the most ubiquitous and diverse group of eukaryotic organisms on Earth, forming a crucial link in terrestrial and freshwater food webs. They have recently become the subject of headlines because of observations of dramatic declines in some places. Although there are hundreds of long‐term insect monitoring programs, a global database for long‐term data on insect assemblages has so far remained unavailable. In order to facilitate synthetic analyses of insect abundance changes, we compiled a database of long‐term (≥10 yr) studies of assemblages of insects (many also including arachnids) in the terrestrial and freshwater realms. We searched the scientific literature and public repositories for data on insect and arachnid monitoring using standardized protocols over a time span of 10 yr or longer, with at least two sampling events. We focused on studies that presented or allowed calculation of total community abundance or biomass. We extracted data from tables, figures, and appendices, and, for data sets that provided raw data, we standardized trapping effort over space and time when necessary. For each site, we extracted provenance details (such as country, state, and continent) as well as information on protection status, land use, and climatic details from publicly available GIS sources. In all, the database contains 1,668 plot‐level time series sourced from 165 studies with samples collected between 1925 and 2018. Sixteen data sets provided here were previously unpublished. Studies were separated into those collected in the terrestrial realm (103 studies with a total of 1,053 plots) and those collected in the freshwater realm (62 studies with 615 plots). Most studies were from Europe (48%) and North America (29%), with 34% of the plots located in protected areas. The median monitoring time span was 19 yr, with 12 sampling years. The number of individuals was reported in 129 studies, the total biomass was reported in 13 studies, and both abundance and biomass were reported in 23 studies. This data set is published under a CC‐BY license, requiring attribution of the data source. Please cite this paper if the data are used in publications, and respect the licenses of the original sources when using (part of) their data as detailed in Metadata S1: Table 1.

Moving from Latent to Manifest Problem: Trajectories Across Scientific and Public Salience of Invasive Alien Species - J. Vaas; P. P. J. Driessen; M. Giezen; F. van Laerhoven; M. J. Wassen (Environmental Management, 2021)
Who worries first about an invasive alien species: scientists or the general public, or do both become concerned simultaneously? Taking thirteen invasive alien species in the Netherlands, this article reconstructs the development of their public and scientific salience: the attention they attracted and the knowledge about them. Salience was assessed from the number of publications from 1997 onwards in the LexisNexis newspaper database and Scopus scientific database. Three trajectories were derived for a species to move from being a latent problem with low salience toward a manifest status with high public and scientific salience. In the most common trajectory, scientific salience increased first, followed by an increase in public salience. We probed the merit of this concept of trajectories by examining the action undertaken for a representative species of the trajectories. We assigned each of these three species a code for inertia and inaction based on the content of a hundred newspaper articles and all available government documents. Knowing the scientific and public salience of these species clarifies why the actions to deal with them differed even though from an ecological perspective they warranted similar attention. The typology of public and scientific salience and the problem trajectories developed in this article together offer a structured approach for understanding an invasive alien species and provide pointers for engaging a community in managing that species.

Early ICU-mortality in sepsis – causes, influencing factors and variability in clinical judgement: a retrospective cohort study - Rob G. H. Driessen; Nanon F. L. Heijnen; Riquette P. M. G. Hulsewe; Johanna W. M. Holtkamp; Bjorn Winkens; Marcel C. G. van de Poll; Iwan C. C. van der Horst; Dennis C. J. J. Bergmans; Ronny M. Schnabel (Infectious Diseases, 2021)

Learning from failure at the science–policy interface for climate action in agriculture - Dhanush Dinesh; Dries Hegger; Joost Vervoort; Bruce M. Campbell; Peter P. J. Driessen (Mitigation and Adaptation Strategies for Global Change, 2021)
Science–policy engagement efforts to accelerate climate action in agricultural systems are key to enable the sector to contribute to climate and food security goals. However, lessons to improve science–policy engagement efforts in this context mostly come from successful efforts and are limited in terms of empirical scope. Moreover, lessons have not been generated systematically from failed science–policy engagement efforts. Such analysis using lessons from failure management can improve or even transform the efficacy of efforts. To address this knowledge gap, we examined challenges and failures faced in science–policy engagement efforts of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). We developed an explanatory framework inspired by Cash et al.’s criteria for successful knowledge systems for sustainable development: credibility, salience, and legitimacy, complemented with insights from the wider literature. Using this framework in a survey, we identified factors which explain failure. To effectively manage these factors, we propose a novel approach for researchers working at the science–policy interface to fail intelligently, which involves planning for failure, minimizing risks, effective design, making failures visible, and learning from failures. This approach needs to be complemented by actions at the knowledge system level to create an enabling environment for science–policy interfaces.

Cerebellar Transcranial Direct Current Stimulation Improves Reactive Response Inhibition in Healthy Volunteers - Syanah C. Wynn; Josi M. A. Driessen; Jeffrey C. Glennon; Inti A. Brazil; Dennis J. L. G. Schutter (The Cerebellum, 2019)

Introducing rewilding to restoration to expand the conservation effort: a response to Hayward et al. - Robert M. Anderson; Robert Buitenwerf; Clemens Driessen; Luísa Genes; Jamie Lorimer; Jens-Christian Svenning (Biodiversity and Conservation, 2019)

Return of the native facilitated by the invasive? Population composition, substrate preferences and epibenthic species richness of a recently discovered shellfish reef with native European flat oysters ( Ostrea edulis ) in the North Sea - M. J. A. Christianen; W. Lengkeek; J. H. Bergsma; J. W. P. Coolen; K. Didderen; M. Dorenbosch; F. M. F. Driessen; P. Kamermans; E. Reuchlin-Hugenholtz; H. Sas; A. Smaal; K. A. van den Wijngaard; et al. (Marine Biology Research, 2018)

The influence of a change in septic shock definitions on intensive care epidemiology and outcome: comparison of sepsis-2 and sepsis-3 definitions - Rob G. H. Driessen; Marcel C. G. van de Poll; Marianne F. Mol; Walther N. K. A. van Mook; Ronny M. Schnabel (Infectious Diseases, 2018)

Governance Conditions for Improving Quality Drinking Water Resources: the Need for Enhancing Connectivity - Susanne Wuijts; Peter P. J. Driessen; Helena F. M. W. Van Rijswick (Water Resources Management, 2018)

Non-targeted workflow for identification of antimicrobial compounds in animal feed using bioassay-directed screening in combination with liquid chromatography-high resolution mass spectrometry - Robin S. Wegh; Bjorn J. A. Berendsen; Wilma D. M. Driessen-Van Lankveld; Mariël G. Pikkemaat; Tina Zuidema; Leen A. Van Ginkel (Food Additives & Contaminants: Part A, 2017)

The implications of succession after fire for the conservation management of moorland invertebrate assemblages - Michael M. Driessen; James B. Kirkpatrick (Journal of Insect Conservation, 2017)

Differences in flood hazard projections in Europe – their causes and consequences for decision making - Z. W. Kundzewicz; V. Krysanova; R. Dankers; Y. Hirabayashi; S. Kanae; F. F. Hattermann; S. Huang; P. C. D. Milly; M. Stoffel; P. P. J. Driessen; P. Matczak; P. Quevauviller; et al. (Hydrological Sciences Journal, 2017)

Recurrent Governance Challenges in the Implementation and Alignment of Flood Risk Management Strategies: a Review - C. Dieperink; D. L. T Hegger; M. H. N. Bakker; Z. W. Kundzewicz; C. Green; P. P. J. Driessen (Water Resources Management, 2016)

Prepared for climate change? A method for the ex-ante assessment of formal responsibilities for climate adaptation in specific sectors - H. A. C. Runhaar; C. J. Uittenbroek; H. F. M. W. van Rijswick; H. L. P. Mees; P. P. J. Driessen; H. K. Gilissen (Regional Environmental Change, 2016)

In memoriam: Wilhelmus Nicolaas Konings (1937–2014) - Arnold J. M. Driessen; Bert Poolman (Extremophiles, 2015)

The saci_2123 gene of the hyperthermoacidophile Sulfolobus acidocaldarius encodes an ATP-binding cassette multidrug transporter - Nuan Yang; Arnold J. M. Driessen (Extremophiles, 2015)

Assessing Stability and Dynamics in Flood Risk Governance - Dries L. T. Hegger; Peter P. J. Driessen; Carel Dieperink; Mark Wiering; G. T. Tom Raadgever; Helena F. M. W. van Rijswick (Water Resources Management, 2014)

Deletion of cdvB paralogous genes of Sulfolobus acidocaldarius impairs cell division - Nuan Yang; Arnold J. M. Driessen (Extremophiles, 2014)

How hyperthermophiles adapt to change their lives: DNA exchange in extreme conditions - Marleen van Wolferen; Małgorzata Ajon; Arnold J. M. Driessen; Sonja-Verena Albers (Extremophiles, 2013)

Exploring the zebrafish embryo as an alternative model for the evaluation of liver toxicity by histopathology and expression profiling - Marja Driessen; Anne S. Kienhuis; Jeroen L. A. Pennings; Tessa E. Pronk; Evert-Jan van de Brandhof; Marianne Roodbergen; Herman P. Spaink; Bob van de Water; Leo T. M. van der Ven (Archives of Toxicology, 2013)

Influence of adaptive evolution of cadmium tolerance on neutral and functional genetic variation in Orchesella cincta - Dalila Costa; Janine Mariën; Thierry K. S. Janssens; Cornelis A. M. van Gestel; Gerard Driessen; José Paulo Sousa; Nico M. van Straalen; Dick Roelofs (Ecotoxicology, 2012)

A New Strategy to Stabilize Oxytocin in Aqueous Solutions: I. The Effects of Divalent Metal Ions and Citrate Buffer - Christina Avanti; Jean-Pierre Amorij; Dewi Setyaningsih; Andrea Hawe; Wim Jiskoot; Jan Visser; Alexej Kedrov; Arnold J. M. Driessen; Wouter L. J. Hinrichs; Henderik W. Frijlink (The AAPS Journal, 2011)

In Vivo Anti-Tumor Effect of Expressing p14ARF-TAT Using a FGF2-Targeted Cationic Lipid Vector - Guoqin Niu; Wouter H. P. Driessen; Sean M. Sullivan; Jeffrey A. Hughes (Pharmaceutical Research, 2011)

The bindosome is a structural component of the Sulfolobus solfataricus cell envelope - Benham Zolghadr; Andreas Klingl; Reinard Rachel; Arnold J. M. Driessen; Sonja-Verena Albers (Extremophiles, 2011)

Enhancing conservation of the Tasmanian glow-worm, Arachnocampa tasmaniensis Ferguson (Diptera: Keroplatidae) by monitoring seasonal changes in light displays and life stages - Michael M. Driessen (Journal of Insect Conservation, 2010)

Comparative study of the extracellular proteome of Sulfolobus species reveals limited secretion - Albert F. Ellen; Sonja-Verena Albers; Arnold J. M. Driessen (Extremophiles, 2010)

“Hot standards” for the thermoacidophilic archaeon Sulfolobus solfataricus - Melanie Zaparty; Dominik Esser; Susanne Gertig; Patrick Haferkamp; Theresa Kouril; Andrea Manica; Trong K. Pham; Julia Reimann; Kerstin Schreiber; Pawel Sierocinski; Daniela Teichmann; Marleen van Wolferen; et al. (Extremophiles, 2010)

Quantification of the Temporal Evolution of Collagen Orientation in Mechanically Conditioned Engineered Cardiovascular Tissues - Mirjam P. Rubbens; Anita Driessen-Mol; Ralf A. Boerboom; Marc M. J. Koppert; Hans C. van Assen; Bart M. TerHaar Romeny; Frank P. T. Baaijens; Carlijn V. C. Bouten (Annals of Biomedical Engineering, 2009)

Real Time, Non-Invasive Assessment of Leaflet Deformation in Heart Valve Tissue Engineering - J. Kortsmit; N. J. B. Driessen; M. C. M. Rutten; F. P. T. Baaijens (Annals of Biomedical Engineering, 2009)

Proteomic analysis of secreted membrane vesicles of archaeal Sulfolobus species reveals the presence of endosome sorting complex components - Albert F. Ellen; Sonja-Verena Albers; Wim Huibers; Angela Pitcher; Cedric F. V. Hobel; Heinz Schwarz; Mihaela Folea; Stefan Schouten; Egbert J. Boekema; Bert Poolman; Arnold J. M. Driessen (Extremophiles, 2009)

A Microstructurally Motivated Model of the Mechanical Behavior of Tissue Engineered Blood Vessels - Shannon L. M. Dahl; Megann E. Vaughn; Jin-Jia Hu; Niels J. B. Driessen; Frank P. T. Baaijens; Jay D. Humphrey; Laura E. Niklason (Annals of Biomedical Engineering, 2008)

Regulation of expression of the arabinose and glucose transporter genes in the thermophilic archaeon Sulfolobus solfataricus - Joanna M. Lubelska; Melanie Jonuscheit; Christa Schleper; Sonja-Verena Albers; Arnold J. M. Driessen (Extremophiles, 2006)

Galantamine: a cholinergic patch in the treatment of alcoholism: a randomized, placebo-controlled trial - K. Mann; K. Ackermann; A. Diehl; D. Ebert; G. Mundle; H. Nakovics; T. Reker; G. Richter; L. G. Schmidt; M. Driessen; K. Rettig; K. Opitz; et al. (Psychopharmacology, 2006)

Tissue Engineering of Human Heart Valve Leaflets: A Novel Bioreactor for a Strain-Based Conditioning Approach - Anita Mol; Niels J. B. Driessen; Marcel C. M. Rutten; Simon P. Hoerstrup; Carlijn V. C. Bouten; Frank P. T. Baaijens (Annals of Biomedical Engineering, 2005)

Functional and structural characterization of the minimal Sec translocase of the hyperthermophile Thermotoga maritima - Monika G. Pretz; Hervé Remigy; Jelto Swaving; Sonja V. Albers; Victoria G. Garrido; Mohamed Chami; Andreas Engel; Arnold J. M. Driessen (Extremophiles, 2005)

Finite Element Model of Mechanically Induced Collagen Fiber Synthesis and Degradation in the Aortic Valve - Ralf A. Boerboom; Niels J. B. Driessen; Carlijn V. C. Bouten; Jacques M. Huyghe; Frank P. T. Baaijens (Annals of Biomedical Engineering, 2003)

Purification and characterisation of a lactococcal aminoacylase - Peter Curley; Chris van der Does; Arnold J. M. Driessen; Jan Kok; D. van Sinderen (Archives of Microbiology, 2003)

Lipid membranes from halophilic and alkali-halophilic Archaea have a low H + and Na + permeability at high salt concentration - J.L.C.M. van de Vossenberg; A. J. M. Driessen; D. Grant; W. N. Konings (Extremophiles, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

The essence of being extremophilic: the role of the unique archaeal membrane lipids - Jack L. C. M. van de Vossenberg; Arnold J. M. Driessen; W. N. Konings (Extremophiles, 1998)

Bioenergetics and cytoplasmic membrane stability of the extremely acidophilic, thermophilic archaeon Picrophilus oshimae - Jack L. C. M. van de Vossenberg; Arnold J. M. Driessen; Wolfram Zillig; W. N. Konings (Extremophiles, 1998)

Mechanism of lantibiotic-induced pore-formation - Gert N. Moll; Gordon C. K. Roberts; Wil N. Konings; Arnold J. M. Driessen (Antonie van Leeuwenhoek, 1996)

Sec-dependent preprotein translocation in bacteria - Tanneke den Blaauwen; A. J. M. Driessen (Archives of Microbiology, 1996)

Secondary transport of amino acids by membrane vesicles derived from lactic acid bacteria - Arnold J. M. Driessen (Antonie van Leeuwenhoek, 1989)

Energetics of glucose uptake in Salmonella typhimurium - M. Driessen; P. W. Postma; K. van Dam (Archives of Microbiology, 1987)

Calcium transport in membrane vesicles ofStreptococcus cremoris - A. J. M. Driessen; K. J. Hellingwerf; W. N. Konings (Antonie van Leeuwenhoek, 1985)

Effect of trypsin treatment of bacteriorhodopsin on its orientation in reconstituted vesicles - A. J. M. Driessen; W. N. Konings (Antonie van Leeuwenhoek, 1985)

Continuous manufacture of yogurt - F. M. Driessen; A. Meijer; J. Ubbels (Antonie van Leeuwenhoek, 1983)

Growth of thermoresistant streptococci in cheese-milk pasteurizers - F. M. Driessen (Antonie van Leeuwenhoek, 1980)